A Scoping Review of Interventions Designed to Support Parents With Mental Illness That Would Be Appropriate for Parents With Psychosis - Radley, Jessica; Sivarajah, Nithura; Moltrecht, Bettina; Klampe, Marie-Louise; Hudson, Felicity; Delahay, Rachel; Barlow, Jane; Johns, Louise C. (Frontiers in Psychiatry, 2022)
The experience of psychosis can present additional difficulties for parents, over and above the normal challenges of parenting. Although there is evidence about parenting interventions specifically targeted at parents with affective disorders, anxiety, and borderline personality disorder, there is currently limited evidence for parents with psychotic disorders. It is not yet known what, if any, interventions exist for this population, or what kinds of evaluations have been conducted. To address this, we conducted a scoping review to determine 1) what parenting interventions have been developed for parents with psychosis (either specifically for, or accessible by, this client group), 2) what components these interventions contain, and 3) what kinds of evaluations have been conducted. The eligibility criteria were broad; we included any report of an intervention for parents with a mental health diagnosis, where parents with psychosis were eligible to take part, that had been published within the last 20 years. Two reviewers screened reports and extracted the data from the included reports. Thirty-seven studies of 33 interventions were included. The findings show that most interventions have been designed either for parents with any mental illness or parents with severe mental illness, and only two interventions were trialed with a group of parents with psychosis. After noting clusters of intervention components, five groups were formed focused on: 1) talking about parental mental illness, 2) improving parenting skills, 3) long-term tailored support for the whole family, 4) groups for parents with mental illness, and 5) family therapy. Twenty-two quantitative evaluations and 13 qualitative evaluations had been conducted but only eight interventions have or are being evaluated using a randomised controlled trial (RCT). More RCTs of these interventions are needed, in addition to further analysis of the components that are the most effective in changing outcomes for both the parent and their children, in order to support parents with psychosis and their families.